Functional Biomaterials for Treatment of Chronic Wound - Zhang, Xi; Shu, Wentao; Yu, Qinghua; Qu, Wenrui; Wang, Yinan; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2020)
The increasing number of patients with chronic wounds caused by diseases, such as diabetes, malignant tumors, infections, and vasculopathy, has caused severe economic and social burdens. The main clinical treatments for chronic wounds include the systemic use of antibiotics, changing dressings frequently, operative debridement, and flap repair. These routine therapeutic strategies are characterized by a long course of treatment, substantial trauma, and high costs, and fail to produce satisfactory results. Biomaterial dressings targeting the different stages of the pathophysiology of chronic wounds have become an active research topic in recent years. In this review, after providing an overview of the epidemiology of chronic wounds, and the pathophysiological characteristics of chronic wounds, we highlight the functional biomaterials that can enhance chronic wound healing through debridement, anti-infection and antioxidant effects, immunoregulation, angiogenesis, and extracellular matrix remodeling. It is hoped that functional biomaterials will resolve the treatment dilemma for chronic wounds and improve patient quality of life.